Octreotide may improve pharyngocutaneous fistula healing through downregulation of cystatins: A pilot study. Issue 1 (28th November 2022) - Cohen, Jonathan; Reed, William; Foster, Matthew W.; Kahmke, Russel R.; Rocke, Daniel J.; Puscas, Liana; Cannon, Trinitia Y.; Lee, Walter T.
Abstract: Background: Pharyngocutaneous fistula (PCF) and salivary leaks are well known complications of head and neck surgery. The medical management of PCF has included the use of octreotide without a well‐defined understanding of its therapeutic mechanism. We hypothesized that octreotide induces alterations in the saliva proteome and that these alterations may provide insight into the mechanism of action underlying improved PCF healing. We undertook an exploratory pilot study in healthy controls that involved collecting saliva before and after a subcutaneous injection of octreotide and performing proteomic analysis to determine the effects of octreotide. Methods: Four healthy adult participants provided saliva samples before and after subcutaneous injection of octreotide. A mass‐spectrometry based workflow optimized for the quantitative proteomic analysis of biofluids was then employed to analyze changes in salivary protein abundance after octreotide administration. Results: There were 3076 human, 332 Streptococcus mitis, 102 G. haemolyans, and 42 Granulicatella adiacens protein groups quantified in saliva samples. A paired statistical analysis was performed using the generalized linear model (glm) function in edgeR. There were and ~300 proteins that had a p  < .05 between the pre‐ and post‐octreotide groups ~50 proteins with an FDR‐corrected p  < .05 between pre‐ and post‐groups. These results were visualized using a volcano plot after filtering on proteins quantified by 2 more or unique precursors. Both human and bacterial proteins were among the proteins altered by octreotide treatment. Notably, four isoforms of the human cystatins, belonging to a family of cysteine proteases, that had significantly lower abundance after treatment. Conclusion: This pilot study demonstrated octreotide‐induced downregulation of cystatins. By downregulation of cystatins in the saliva, there is decreased inhibition of cysteine proteases such as Cathepsin S. This results in increased cysteine protease activity that has been linked to enhanced angiogenic response, cell proliferation and migration that have resulted in improved wound healing. These insights provide first steps at furthering our understanding of octreotide's effects on saliva and reports of improved PCF healing. Abstract : Octreotide has been used historically in the medical management of salivary fistulas without a clear understanding of its therapeutic mechanism. In this investigation, we gave octreotide to healthy volunteers and examined changes in the saliva proteome to better understand the effects of octreotide on the proteomic environment and thus potentially identify potential mechanisms of action for octreotide in the healing of fistula.